Predictive Role of Species Diversity on Aboveground Carbon via Functional Diversity and Dominance in the Moist Afromontane Forest: Implications for Conservation Policies - Ferede Abuye Jeldu; Motuma Tolera; Teshale Woldeamanuel (International Journal of Forestry Research)
The moist Afromontane forest of Ethiopia plays a crucial role in carbon storage and mitigating greenhouse gas (GHG) emissions. To guide effective conservation policies, it is essential to understand the relationship between species diversity and carbon storage in this unique ecosystem. Therefore, this study aimed to evaluate the response of aboveground carbon (AGC) to species and functional diversity and their effects on AGC in the Yayu Coffee Forest Biosphere Reserve (YCFBR). Using different plot sizes, we collected vegetation data from the core, buffer, and transitional zones of the reserve. We selected traits related to plant-life strategy, competition ability, response to disturbances, and climate change. Structural equation models (SEMs) were employed to assess the effects of species diversity, functional diversity, and functional dominance on AGC. Data analysis was conducted using R software. Our results revealed that the effects of species richness on AGC were mediated through functional diversity and functional dominance, as demonstrated by both the full mediation and partial mediation models. This suggests that the selection effects and niche complementarity are mutually exclusive yet equally important for predicting AGC. The findings further indicate that functional diversity and functional dominance together accounted for significant predictors of the AGC by 21% in the YCFBR. From a practical standpoint, findings highlight the importance of conserving species diversity as a means to maintain higher AGC in the tropical moist Afromontane forests. In conclusion, this research significantly contributes to the scientific literature by providing valuable insights into the complex relationship between species diversity and carbon storage. The results emphasize the crucial role of functional diversity and dominance in predicting AGC, underscoring the importance of biodiversity conservation for climate mitigation efforts. These findings have practical implications for the development of effective conservation policies tailored to protect and sustain the carbon storage potential of this unique ecosystem.